Advances in Medical and Surgical Cornea From Diagnosis to Procedure - Jeng, Bennie H. (Essentials in Ophthalmology, 2014)
This book presents up-to-date information on the diagnosis and management of the spectrum of medical and surgical corneal diseases, with a special focus on new technology. The latest tools for diagnosing ocular surface disease, infectious keratitis, and ocular allergies are discussed, along with novel treatment options for these entities. The impact of progress in imaging and contact lens technology on the management of corneal conditions is fully described, and the efficacy of corneal collagen crosslinking for keratoconus and corneal ectasia is evaluated. Detailed attention is devoted to the latest surgical techniques, including lamellar keratoplasty, endothelial keratoplasty, keratoprosthesis, and laser-assisted penetrating keratoplasty. In addition, the role of the eye bank in facilitating corneal procedures is explained. Advances in Medical and Surgical Cornea is written by leading authorities who share a passion for effective, cutting-edge care. It will be invaluable for both experienced ophthalmologists and trainees.